1993
DOI: 10.1021/jf00036a008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of oxidation during washing improves the functionality of bovine cardiac myofibrillar protein.

Abstract: The effect of antioxidative treatments during bovine cardiac myofibril isolation on rheological and gelling properties of the myofibrillar protein was examined. Minced beef heart muscle was washed four times in 25 mM phosphate buffer (pH 7.0) without (control wash) or with combined antioxidants (0.02% propyl gallate, 0.2 % sodium ascorbate, and 0.2 ' % sodium tripolyphosphate). Washing with antioxidants inhibited oxidation in fresh myofibrillar pellets and in pellets stored for up to 8 days. The antioxidant tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 17 publications
3
35
0
Order By: Relevance
“…However, functional properties were largely protected by cryoprotectants as well as at Ϫ70ЊC independent of cryoprotectants. Thus, unless extremely low temperatures are used, beef heart surimi subjected to long-term cryogenic storage should be mixed with cryoprotectants and antioxidants to preserve functionality.the methods of Wan et al (1993). The pellet of BHS was diluted to a protein concentration of 50 mg/mL with 0.6M NaCl, 50 mM sodium phosphate buffer (pH 6.0).…”
mentioning
confidence: 99%
“…However, functional properties were largely protected by cryoprotectants as well as at Ϫ70ЊC independent of cryoprotectants. Thus, unless extremely low temperatures are used, beef heart surimi subjected to long-term cryogenic storage should be mixed with cryoprotectants and antioxidants to preserve functionality.the methods of Wan et al (1993). The pellet of BHS was diluted to a protein concentration of 50 mg/mL with 0.6M NaCl, 50 mM sodium phosphate buffer (pH 6.0).…”
mentioning
confidence: 99%
“…; Wan et al . ) and could be explored in the further study. Jiang and Xiong () suggested that a 7‐h incubation with MTGase accentuated the gel‐strengthening effect by these SPI samples.…”
Section: Resultsmentioning
confidence: 99%
“…Washing removes a substantial portion of these prooxidants, and the incorporation of propyl gallate in the washing process can effectively block lipid oxidation by terminating free radical chain reactions. Previous studies (Wan et al, 1993;Xiong et al, 1993;Srinivasan et al, 1996) showed that propyl gallate was highly capable of inhibiting TBARS formation in BHS during short-term storage at refrigeration temperatures. Our results demonstrated that propyl gallate was also effective during long-term storage at sub-freezing temperatures.…”
Section: Results and Discussion Lipid Oxidationmentioning
confidence: 99%